Application of autologous platelet-rich gel formed by calcium gluconate combined with hormone therapy for endometrial repair after hysteroscopic transcervical resection of adhesion surgery and successful pregnancy: case report and literature review - Li, Yunying; Han, Yingxue; Su, Xiaojuan; Cao, Junjuan; Liu, Junxia; Zhang, Wenjuan (Frontiers in Medicine, 2024)
Introduction: Intrauterine adhesion (IUA), a common gynecological disease, is mainly caused by traumatic or infectious factors that lead to basal endometrial layer physiological repair disorders. IUA is mostly treated via hysteroscopic transcervical resection of adhesion and although it can restore uterine cavity shape, its endometrial repair effectiveness is limited. The figures showed that after surgery, patients with IUA have a high recurrence rate. Therefore, quick endometrial damage repair is key to successful treatment.Case presentation: A 34-year-old patient visited our hospital after experiencing amenorrhea for four months following an induced abortion and had a fertility requirement. Based on the American Fertility Society intrauterine scores, the patient was diagnosed with moderate IUA. She underwent transcervical resection of adhesion, followed by autologous platelet-rich gel intrauterine perfusion and periodic estrogen-progesterone treatment for three menstrual cycles. No complications developed during treatment and the patient's endometrium was significantly repaired, with successful pregnancy being achieved.Autologous platelet-rich gel promoted endometrial repair and acted as a mechanical barrier to prevent intrauterine adhesion. This approach may offer new insights into IUA treatment..